Teachers’ and Student’s Scaffolding in Second Language Learning - Aziza Restu Febrianto (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2019)
The aim of this paper is to show how scaffolding from teacher to students and that from students to students work during a sequence of language learning in which communication skills and fluency are the goals to reach. Pedagogical sequence that includes the roles of teacher in facilitating students involved in various types of learning activity and tasks has been analysed to find educational implications of the theories. Based on the data of some empirical studies, it shows that the strategy used by teacher to facilitate the activities and give corrective feedbacks is very helpful to make students focus on the goals. This is how scaffolding from teacher works efficiently in classroom learning. Pair and group work interactions among students with different characteristics also prove how scaffolding from students to students are present and contributes to the communication skills development. However, not all students can provide useful scaffolding for others due to their different personality. In conclusion, the teacher’s scaffolding and students’ scaffolding occur in different patterns (Storch 2002: 119-158). Teacher’s scaffolding comes in a various range of support, while student’s scaffolding might be helpful, but not as significantly as that of the teacher.